2013
DOI: 10.1158/0008-5472.can-12-4331
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing the Treatment of Pediatric Medulloblastoma: Polo-like Kinase 1 as a Molecular Target in High-Risk Children

Abstract: Medulloblastoma is the most common malignant brain tumor in children. This disease is heterogeneous and is composed of four subtypes of medulloblastoma [WNT, Sonic Hedgehog (SHH), Group 3, and Group 4]. An immediate goal is to identify novel molecular targets for the most aggressive forms of medulloblastoma. Polo-like kinase 1 (PLK1) is an oncogenic kinase that controls cell cycle and proliferation, making it a strong candidate for medulloblastoma treatment. In this study, pediatric medulloblastomas were subty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 41 publications
1
67
0
1
Order By: Relevance
“…DAOY cells have a gene expression profile consistent with a type 2 (Hh-subtype) medulloblastoma and accordingly exhibit elevated Hh signaling (40). In these cells, MBZ caused a reduction in GLI1 expression with an IC 50 =516 ±81 nM (SEM; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DAOY cells have a gene expression profile consistent with a type 2 (Hh-subtype) medulloblastoma and accordingly exhibit elevated Hh signaling (40). In these cells, MBZ caused a reduction in GLI1 expression with an IC 50 =516 ±81 nM (SEM; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1B). Notably, DAOY xenografts exhibit large cell morphology (40), which in naturally-evolving tumors is associated with poor outcomes (41). …”
Section: Resultsmentioning
confidence: 99%
“…The observation of increased PI3K pathway activity in tumors that develop resistance to SMOis (63,64), along with reports of recurrent mutations affecting this pathway (12,42), has suggested that PI3K inhibition may be an important strategy for preventing or overcoming resistance of SHH-MB. Finally, preclinical studies have suggested that Polo-like kinase inhibitors may be particularly effective in SHH-MB (71,72). The heterogeneity of driver mutations and resistance mechanisms even within the SHH-MB subgroup suggests that careful patient selection and a diversity of therapeutic approaches will be necessary to effectively target this disease.…”
Section: Shh Subgroupmentioning
confidence: 99%
“…[11][12][13][14] BI2536 is an ATP-competitive Plk1 kinase inhibitor and has been used in phase II clinical studies in breast cancer, endometrial cancer, head and neck cancer, melanoma, ovarian cancer and sarcoma. 15 In prostate cancer, Plk1 knockdown by RNAi causes induction of mitotic catastrophe, 16 suggesting that Plk1 might be a target and BI2536 might be a potential drug of PCa treatment.…”
Section: Introductionmentioning
confidence: 99%